PENGARUH GAYA KEPEMIMPINAN, PEMAHAMAN GOOD GOVERNANCE, BUDAYA ORGANISASI, INDEPENDENSI AUDITOR, DAN PENGALAMAN KERJA TERHADAP KINERJA AUDITOR (Studi Empiris Pada KAP Di Semarang) - Finansius Lalaar, 12.05.52.0113; Alfasadun, Alfasadun (Students' Journal of Accounting and Banking, 2016)
This study examined the influence of leadership style, understanding of good governance, organizational culture, auditor independence and work experience on the performance of auditors (Empirical Study on Kantor Akuntan Publik ( KAP ) in Semarang). This study used six variables: leadership style, understanding of good governance, organizational culture, auditor independence, work experience, and performance of auditors. The population in this study is the auditor who worked on KAP in Semarang. The research sample was obtained through census method on KAP in Semarang. Data collection techniques using questionnaires filled out by the respondents that the auditors. The total sample were obtained and used in the study was 40. The collected data is then processed using statistical tools that IBM SPSS Statistics 20.0. Initial testing conducted are validity test data from each question, followed by a reliability test using alpha conbrach. Regression analysis was performed to test partially thereafter each independent variable were tested using the F test and the coefficient of determination (R2). The results obtained are leadership style, understanding of good governance, organizational culture, and the independence of the auditor does not affect the performance of auditors while working experience affect the performance of auditors.  Keywords: Leadership Style, Understanding of Good Governance, Organizational Culture, The Independence of The Auditor, The Performance of Auditors